[A visual guide to the world’s greatest challenges] (Washington, D.C.,Glasgow, 2007)
Prepared by the Development Data Group of the World Bank, this atlas distills global development statistical indicator into colorful and relatively simple maps, tables, and charts, presented together with brief textual explanations. Every map presented is a standardized political map of the world, with countries shaded and colored in order to convey information on national incomes, demographic change, education, health, economic development, and the environment. Typically, these maps are accompanied by more individualized charts, tables, graphs, et cetera that relay the same or related information in different form, as well as various information side boxes
Keywords: Developing countries,Globalization,Gross national product,Population,Economic indicators; Statistics.,Statistics,Maps,Maps,Maps